Effectiveness of the Conservative Surgical Management of the Ameloblastomas: A Cross-Sectional Study - Rocha, André Caroli; Fonseca, Felipe Paiva; Santos-Silva, Alan Roger; Lourenço, Silvia Vanessa; Ceccheti, Marcelo Minharro; Júnior, Jayro Guimarães (Frontiers in Oral Health, 2021)
Ameloblastoma is a benign, but locally aggressive odontogenic neoplasm, whose appropriate therapeutic management remains highly debatable. The aim of this study was to evaluate the reliability and effectiveness of two conservative surgical therapeutic protocols (curettage only and curettage plus cryotherapy) for the management of ameloblastomas. Fifty-three cases of ameloblastomas treated in a 9-year period were retrospectively analyzed regarding their clinic, histopathologic, radiographic and therapeutic data. The results and the postoperative complications related to both therapeutic protocols were also statistically investigated. A slight female preponderance was seen (1.12:1.0), with a mean age of 27.1 years. Posterior mandible was the most affected site and dental involvement was frequently found. Multilocular lesions causing bone cortices alterations were the most common radiographic findings. Recurrences were seen in 9.4% of the cases and although patients submitted to curettage plus cryotherapy have shown an increased incidence of dehiscence, infection and paresthesia, only bone sequestration proved to be significantly more frequent in this group than in patients treated by curettage only. The incidence of recurrences following conservative management is low and cryotherapy use as an adjuvant tool must be rationally considered.